Cardiac sympathetic denervation in wild-type transthyretin amyloidosis. (25th November 2020) - Aimo, A; Gimelli, A; Vergaro, G; Genovesi, D; Kusch, A; Emdin, M; Marzullo, P
Abstract: Background: Tissue accumulation of misfolded transthyretin (TTR) may occur because of TTR gene mutations (variant amyloid TTR amyloidosis, ATTRv), or as an age-related phenomenon (wild-type ATTR, ATTRwt). Cardiac sympathetic denervation has been reported in ATTRv, but has never been investigated in ATTRwt. Methods: Fifteen consecutive patients with ATTRwt cardiomyopathy (81% men, median age 82 years, no one with prior myocardial infarction) underwent Cadmium Zinc Telluride tomographic imaging for amyloid burden (99mTc-hydroxymethylene diphosphonate - 99mTc-HMDP), innervation (123I-metaiodobenzylguanidine – 123I-MIBG), and perfusion (99mTc-tetrofosmin). Results: Median summed 99mTc-HMDP score was 60 (58–62), denoting a severe and diffuse amyloid burden. Planar 123I-MIBG examination showed decreased early and late H/M ratios (late H/M ratio: 1.5 [1.3–1.6], range 1.2–1.9, reference value ≥2.0). Summed 123I-MIBG score was 12 (6–22), with the most prominent denervation in the infero-septal, inferior, and infero-lateral regions; summed rest score was 7 (5–11), with lowest degrees of myocardial perfusion in the inferior and infero-septal regions. The correlation between amyloid burden (as relative 99mTc-HMDP uptake) and innervation (as relative 123I-MIBG uptake) did not achieve statistical significance at both segmental (p=0.252) and regional level (p=0.251). Nevertheless, denervation tended to worsen in parallel with the amyloid burden, and 123I-MIBG scores increased with 99mTc-HMDP scores. Segments and regions with more prominent hypoperfusion were those showing the more intense denervation (r=0.500 and 0.591, respectively; both p<0.001). Conclusions: Patients with ATTRwt cardiomyopathy display cardiac sympathetic denervation, particularly in the inferior and septal myocardial wall. Myocardial hypoperfusion has a similar regional pattern, while the amyloid burden is more extensive. Funding Acknowledgement: Type of funding source: None